Prevalence and evolution of clinical cases of Yellow Fever in Brazil between the years 2007 to 2016 (Research, Society and Development, 2022)
Yellow Fever (YF) is a non-contagious infectious disease of variable symptoms that occurs mainly in tropical forests regions of the Americas and Africa and is caused by a Flavivirus belonging to the Flaviviridae family. Its vectors are mosquitoes of the genus Haemagogus, Sabethes and Aedes, and these have non-human primates as the main source of infection. In Brazil, there has been no record of urban AF since 1942, although the increase in cases of the wild form combined with low vaccination coverage contribute to the risk of re-urbanization of the disease Material and methods: For the study, epidemiological data were obtained from confirmed cases of Yellow Fever reported in the Notification System for Health Disorders (SINAN) available at the Informatics Department of the Unified Health System (DATASUS). Results and discussion: A total of 177 cases of were reported in Brazil, the year with the highest notification was in 2016 (52). The region with the highest occurrence of cases were the Southeast (95). Regarding the clinical evolution, of the 177 cases, 68 affected patients were cured, while 89 died from the reported injury, evidencing a high rate of lethality (50.2%). Conclusion: YF remains a public health problem, over the years there was a decrease in cases, this was due to immunization campaigns in the country, however, there was a significant increase in notifications in 2016, this whole panorama reinforces the need intensifying surveillance and expanding vaccine coverage.